Mobile and Contextual Learning: A Case Study on Mobile Didactics in Teaching and Education - Kranz, Matthias; Möller, Andreas; Diewald, Stefan; Roalter, Luis; Beege, Barbara; Meyer, Barbara; Hendrich, Andreas (International Journal of Mobile Learning and Organisation, 2013)
martphones, as ubiquitous companions in all activities of daily living (ADLs), have also been adopted in educational contexts. Mobile applications go along with novel interfaces and ways of interaction, converging towards the vision of Ubiquitous Computing (Weiser, 1998). In this article, we provide an up-to-date overview of the demand on mobile services in higher education and learning environments grounded on two large-scale studies. We investigated the current use and the demand of online campus services among students and academic staff at a university of technology. In a follow-up study, we focused on the demand of mobile learning applications. We identified requirements for a didactics application in higher education as an example for ubiquitous mobile learning support. We introduce the MobiDics application, describe its didactic foundation and its implementation. MobiDics allows ubiquitous didactic training, adapted to personal needs and contexts. We conclude by outlining some future perspectives for didactic teaching suppor
Keywords: mobile learning; context-based learning; mobile interaction